O foot-ball de todos: uma história social do futebol em Porto Alegre, 1903-1918 - Soares, Ricardo Santos (2014)
Before becoming the most practiced sport of the present day, football experienced a broad and complex process of spatial diffusion, coming from Victorian England towards the most diverse regions of the planet. Characterized as a sport of the elite, it arrives in Brazil in this same condition, however it experiences in Rio Grande do Sul a unique "appropriation". Pointing out the differences in origin in comparison with the rest of the country, this work focuses on the particularity that was historically translated as a "construction of national identity," which in the south of Brazil also emerges by the hands of the elite, who was composed of teutos immigrants. At the same time the sport is rapidly absorbed by a portion of the city s black community. The outcome of this research unveiled the importance of the black ethnicity, which combined with the elite and the large number of immigrants, introduces a type of football to Porto Alegre with an important role in the process of ideological identification. This process turns football players into representative symbols of social groups. It has also been concluded as a historical product, that there has been a new existent relationship of identification between the spectators and their clubs, giving birth to supporters. In this sphere, Gremio and Internacional are born, an event which will later be appropriated by the capitalist system, taking this "passion" and turning it into a commodity. For its feasibility the research points to the necessity of a broad debate about the suitability of football in the business world, while suggesting in this context the role of historians. This role should not be to legitimize fabricated traditions, but rather to provoke a critical analysis of this highly popular sport, avoiding the subterfuge of shallow narratives and allowing the chronicle to exceed its limits.